Glucagon-like peptide-1 receptor agonists as a Therapeutic Option for Antipsychotic-Induced Obesity: A Review of Current Evidence - Gniaź, Natalia; Górska, Aleksandra; Grela, Wiktor; Niewiadomska, Jagoda; Furtak, Daria; Tulej, Dawid; Głogowska, Paulina; Dziedzic, Alicja; Marciniuk, Dominika; Marko, Natalia (Journal of Education, Health and Sport, 2024)
Introduction Obesity affects over 650 million adults worldwide and is a major risk factor for cardiovascular diseases and type 2 diabetes. Among those affected are patients treated with antipsychotics, such as clozapine and olanzapine, which often lead to significant weight gain, increasing the risk of metabolic syndrome. Recent advances with glucagon-like peptide-1 receptor agonists (GLP-1 RAs), including semaglutide and liraglutide, show promise in addressing antipsychotic-induced obesity by reducing weight and improving metabolic health. Purpose The aim of this review is to present an overview of the current state of knowledge regarding the efficacy of GLP-1 RAs in the treatment of antipsychotic-induced obesity. Materials and methods This review is based on both original research studies and review articles identified through a comprehensive search of the PubMed database, using the following search terms: obesity, antipsychotic-induced weight gain, clozapine, olanzapine, adverse effect, GLP-1 receptors agonist. Description of the state of knowledge GLP-1 RAs significantly reduce body weight and adipose tissue by suppressing appetite, particularly for high-fat foods. Clinical trials show improvements in lipid profiles, blood pressure, and inflammation, contributing to better metabolic health. However, their long-term effects, especially with different antipsychotics, remain insufficiently studied. Conclusions GLP-1 RAs show significant potential for managing antipsychotic-induced obesity, but further research is needed to assess long-term efficacy and safety in this population.